Pengenalan Tumbuhan Khas Kalimantan Tengah Kepada Anak Sebagai Upaya Melestarikan Kearifan Lokal Dalam Kegiatan Ecoprint - Ervina; Afifah, Neela; Fransiska, Yulia (Yayasan Sagita Akademia Maju, 2024)
This community service aims to introduce local wisdom typical of Central Kalimantan through the Kelakai plant. This community service activity is integrated with learning, making ecoprinting a learning activity that can be used to introduce the Kelakai plant and help stimulate children's physical motor development. This is also done as an effort to preserve local wisdom in Central Kalimantan. The targets for community service participants are children aged 5-6 years old class B 2 Yusuf bin Yaqub who are at PAUD IT Al Ghazali Modern School Palangka Raya and students of MBKM (Free Learning Independent Campus) Early Childhood Islamic Education Study Program Faculty Tarbiyah and Teacher Training IAIN Palangka Raya are also actively involved in these activities. The results of community service at PAUD IT Al Ghazali Modern School Palangka Raya regarding introducing children to plants originating from Central Kalimantan show that children can get to know one of the local wisdom typical of Central Kalimantan, namely the Kelakai plant, and children also get stimulation in aspects of physical development motor.